A new education for a new economy : from human capital to human flourishing - Gilead, Tal (New York : Routledge, 2024)
"Providing an in-depth, novel analysis of education's role in today's economy by scrutinizing its theoretical underpinnings, this volume critiques the suitability of the current, dominant economic framework for education and for shaping educational policymaking worldwide. Critically examining the history and philosophy that underpin our present societal understanding of the link between economics and education, the book argues for an urgent redefining of education's role in the economy, based on intellectual foundations that significantly differ from our current, dominant conceptions. Across seven chapters, the book posits that the adoption of a new philosophical framework, the reshaping of economic and educational aims, and the adjustment of our educational system are each necessary to better promote human flourishing. Ultimately providing a platform to entirely reconsider the idea that the primary aim of education is to serve the economic system - in particular, economic growth - this book will appeal to scholars, researchers and postgraduate students studying educational policy, the philosophy of education, and the history of education more broadly. Education policymakers and academics studying education and the economy may also find this book of interest"--
The economy and education -- How education became an economic priority -- Rethinking the place of normativity and prediction in economics and education -- Conflicting account of well-being and implications for education -- On what human behavior is and ought to be -- A new economic perspective on education -- Some final thoughts on the past and future.
Keywords: Education -- Economic aspects; Economic development -- Effect of education on; Educational planning; Manpower policy; Education and globalization; EDUCATION / General; EDUCATION / Educational Policy & Reform / General; EDUCATION / Philosophy & Social Aspects